Investigation of nuclear chronometer time decay characteristics for revision of age of astrophysics objects - Doroshko, N.L.; Dolinska, M.E. (Вопросы атомной науки и техники, 2004)
The new algorithm for the determinations of the characteristics functions of the energy distribution, decay probability, decay intensities and life times of the excited levels is proposed. Quantum-mechanical motivation of the needing of the time characteristics revising for the nuclear-chronometers it is given. Calculations for concrete decay events of the nuclei ²³⁸U, ²³2Th, ²³⁵U at room and stars temperatures, with and without account ofthe Doppler effect were conducted. Запропоновано новий алгоритм для визначення характеристичних функцій розподілу по енергії, ймовірностей розпаду, інтенсивності розпаду і часу життя збуджених станів рівнів. Зроблено квантовомеханічне обгрунтування необхідності перегляду часових характеристик ядер-хронометрів. Проведені розрахунки для конкретных випадків розпаду ядер ²³⁸U, ²³2Th, ²³⁵U при кімнатних і зоряних температурах з урахуванням ефекту Доплера та за його відсутності Предложен новый алгоритм для определения характеристических функций распределения по энергии, вероятности распада, интенсивности распада и времени жизни возбужденных состояний уровней. Дано квантовомеханическое обоснование необходимости пересмотра временных характеристик ядер-хронометров. Проведены расчеты для конкретных случаев распада ядер ²³⁸U, ²³2Th, ²³⁵U при комнатных и звездных температурах с учетом эффекта Доплера и при его отсутствии.